2023
DOI: 10.1038/s41467-023-38209-x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel dressing integrating FAK inhibition and ROS scavenging for mechano-chemical treatment of atopic dermatitis

Abstract: Atopic dermatitis (AD) is a chronic skin disease caused by skin immune dyshomeostasis and accompanied by severe pruritus. Although oxidative stress and mechanical scratching can aggravate AD inflammation, treatment targeting scratching is often overlooked, and the efficiency of mechano-chemically synergistic therapy remains unclear. Here, we find that enhanced phosphorylation of focal adhesion kinase (FAK) is associated with scratch-exacerbated AD. We then develop a multifunctional hydrogel dressing that integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 74 publications
1
24
0
Order By: Relevance
“…16,17 In addition, severe itching and repetitive scratching disrupt epidermal barriers; thus the increment of ROS is more likely to cause cumulative skin damage in AD lesions and aggravate itch sensitization through the itch−scratch cycle. 16,18 Our findings further confirm that ROS is upregulated in MC903-induced AD-like lesions in mice (Figure S1), and the literature reports also demonstrate that ROS are overproductive in the serum of AD patients compared to normal individuals. 19 Given the importance of ROS in AD pathophysiology, modulating the complex mechanochemical coupling environment by scavenging ROS may be a promising therapeutic strategy for AD management.…”
Section: ■ Introductionsupporting
confidence: 88%
“…16,17 In addition, severe itching and repetitive scratching disrupt epidermal barriers; thus the increment of ROS is more likely to cause cumulative skin damage in AD lesions and aggravate itch sensitization through the itch−scratch cycle. 16,18 Our findings further confirm that ROS is upregulated in MC903-induced AD-like lesions in mice (Figure S1), and the literature reports also demonstrate that ROS are overproductive in the serum of AD patients compared to normal individuals. 19 Given the importance of ROS in AD pathophysiology, modulating the complex mechanochemical coupling environment by scavenging ROS may be a promising therapeutic strategy for AD management.…”
Section: ■ Introductionsupporting
confidence: 88%
“…With the increase of Cur-Car-IL content, the tensile strength and Young's modulus of the hydrogel gradually increase, while the elongation at break decreases (Figure 1k). 6,7,37 These results indicated that the Cur-Car-IL@Ilo hydrogel has good stability, sustained release, and mechanical properties, which have potential application value for the drug delivery carrier of psoriasis. the on-demand release of drugs from hydrogel and the penetration of drugs on the skin (Figure 2a).…”
Section: Resultsmentioning
confidence: 80%
“…Apart from cytokine-induced EndoMT, another interesting area to investigate will be the effect of melanin/ polydopamine NPs on reactive oxygen species (ROS) induced EndoMT given the ROS scavenging property of melanin/ polydopamine NPs. 72 The interaction of nanoparticles and endothelial cells has been increasingly under scrutiny since the endothelium lies in direct contact with nanoparticles in the blood circulation, regardless of whether the nanoparticles are intentionally injected for medical purposes or unintentionally introduced due to undesired exposure. Under most circumstances, the exposure of endothelial cells to nanoparticles can exert dosedependent detrimental effects on the endothelium and further lead to other unwanted pathological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the potential of this work goes far beyond atherosclerosis and cancer treatments considering the importance of EndoMT in the development of organ fibrosis and the prevalence of N-cadherin on various endothelial-derived mesenchymal cells. , As such, future work will focus on validating this approach in the context of reversing organ fibrosis. Apart from cytokine-induced EndoMT, another interesting area to investigate will be the effect of melanin/polydopamine NPs on reactive oxygen species (ROS) induced EndoMT given the ROS scavenging property of melanin/polydopamine NPs …”
Section: Discussionmentioning
confidence: 99%